2007
DOI: 10.1109/tcad.2006.887925
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to Technology Mapping for LUT-Based FPGAs

Abstract: The paper presents several improvements to state-of-theart

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 19 publications
0
76
0
Order By: Relevance
“…Previous work [12] has shown that applying two complementary heuristics, as shown in Figure 3.3, in the given order produces good practical results. The first heuristic (area flow) has a global view and selects logic cones with more shared logic.…”
Section: Area Recoverymentioning
confidence: 96%
See 3 more Smart Citations
“…Previous work [12] has shown that applying two complementary heuristics, as shown in Figure 3.3, in the given order produces good practical results. The first heuristic (area flow) has a global view and selects logic cones with more shared logic.…”
Section: Area Recoverymentioning
confidence: 96%
“…A standard technique to map into K-input LUTs uses cutenumeration [8][17] [6] [12]. In this approach, the subject graph is traversed in a topological order.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This need increases the interest for transistorlevel (or "switch-level") CAD tools for digital VLSI design. Traditional approaches and tools work at the gate level and produce optimized Boolean expressions with respect to constraints such as area, delay and power that are then mapped to platforms such as Programmable Logic Devices (i.e., PLAs, PALs, FPGAs) or standard cells (see, e.g., [18], [10], [3], [20], [9], [17], [1], [6], [19], [4], [8], [5], [25], [28], [23], [24]). The design effort is thus greatly reduced but the area and performance are compromised when compared to what can be achieved by a customized transistor-level approach.…”
Section: Introductionmentioning
confidence: 99%